Outgroup evaluation and social identity among boys and girls as related to parental occupation and residence - Afroz, Nazma (Journal of Life and Earth Science, 2011)
The study attempted to investigate social identity and out-group evaluation in adolescent boys and girls in relation to parental occupation and residential background. The study used a sample composed of 320 respondents. An Adjective Check List was used for data collection. A three way analysis of variance involving 2 levels of gender (boys/girls), 2 levels of parental occupation (business/service) and 2 levels of residence (urban/rural) was used for the computation of results. Results showed gender, parental occupation and residence had statistically significant effects on the respondents. A two-way interaction between profession and residence was also statistically significant. Respondents with service background evaluated out-group significantly less positively as compared to the respondents with business background. Again, girls evaluated out-group significantly less positively as compared to the boys. Moreover, respondents with urban residence evaluated out-group significantly less positively as compared to the respondents with rural residence. Key words: Social identity; self-depreciation; parental occupation; misidentified perception; racial identification. DOI: 10.3329/jles.v5i0.7351 J. Life Earth Sci., Vol. 5: 57-61, 2010